Analisis gaya belajar di rumah selama pandemi covid-19 dalam mata pelajaran bahasa Indonesia pada siswa kelas V di sekolah dasar - Zahrah, Ukhtia Amalia; Sukarno, Sukarno; Sriyanto, Muhammad Ismail (Didaktika Dwija Indria, 2021)
Abstract. This research aims to determine the types of student learning styles, problems in the application of learning styles, and the results of implementing learning styles at home during the COVID-19 pandemic in the content of Indonesian language. This research used a descriptive qualitative method with the subject of 15 students in 5th grade Pajang 4 Surakarta elementary school. This research was implemented in 1st semester using a questionnaire distributed to students via google form. Besides that, researchers also conducted interviews with teachers and documentation to support the research. Technique triangulation and time triangulation were selected as tests for the validity of the data in this research. The stages of data analysis used the Miles and Huberman data analysis model. In this research, the results showed that the 5th grade students of Pajang 4 Surakarta elementary school who chose the auditory learning style had a percentage of 20%. Then students with a tendency to visual learning styles have a percentage of 33.33%. Meanwhile, the combined learning style between auditory and visual has the highest percentage of 46.66%. In conclusion, most of the 5th grade students of Pajang 4 Surakarta elementary school used a combined auditory and visual learning style.Keywords: learning style, online learning, Indonesian language, COVID-19, elementary school